The Occluded Artery Trial (OAT) Viability Ancillary Study (OAT-NUC): Influence of Infarct Zone Viability on Left Ventricular Remodeling After Percutaneous Coronary Intervention vs. Optimal Medical Therapy Alone - Udelson, James E (2011)
BACKGROUND: The Occluded Artery Trial (OAT) showed no difference in outcomes between percutaneous coronary intervention (PCI) vs. optimal medical therapy (MED) in patients with persistent total occlusion of the infarct related artery (IRA) 3–28 days post-MI. Whether PCI may benefit a subset of patients with preservation of infarct zone (IZ) viability is unknown. METHODS AND RESULTS: The OAT nuclear ancillary study hypothesized that; 1) IZ viability influences left ventricular (LV) remodeling, and that 2) PCI as compared to MED attenuates adverse remodeling in post-MI patients with preserved viability. Enrolled were 124 OAT patients, who underwent resting nitroglycerin-enhanced (99m)Tc sestamibi SPECT prior to OAT randomization, with repeat imaging at 1 year. All images were quantitatively analyzed for infarct size, IZ viability, LV volumes and function in a core lab. At baseline, mean infarct size was 26%±18 of the LV, mean IZ viability was 43%±8 of peak uptake, and the majority (70%) of patients had at least moderately retained IZ viability. There were no significant differences in 1-year EDV or ESV change between those with severely reduced vs. moderately retained IZ viability, or when compared by treatment assignment PCI vs. MED. In multivariable models, increasing baseline viability independently predicted improvement in EF (p=0.005). There was no interaction between IZ viability and treatment assignment for any measure of LV remodeling. CONCLUSIONS: In the contemporary era of optimal medical therapy, PCI of the IRA compared to medical therapy alone does not impact LV remodeling irrespective of IZ viability.